Site Location Optimization of a Tower Crane Through Building information Modeling (BIM). - Xu Shen; Marks, Eric (Journal of Safety, Health & Environmental Research, 2017)
Construction site layout planning can be described as a multi-criteria optimization problem that is traditionally resolved using two-dimensional project data. Although construction researchers have investigated construction site layout methods, few studies have identified methods of optimization for crane location selection based on safety and productivity. This research creates a framework within a building information model (BIM) to optimize the two-dimensional location of a tower crane for a given construction site. The created algorithms optimize the tower crane's location based on safety and productivity constraints specifically that 1) the tower crane must access the majority of material in the lay down area and the structure and 2) the crane boom coverage radius over a travel pathway is minimized. By optimizing the location of the tower crane in an existing BIM, hazardous conditions can be decreased by identifying and mitigating situations in which a load lifted by the tower crane crosses the travel path of equipment and pedestrians. The contribution of this research is an implementable framework in BIM that can automatically identify the optimal location of a tower crane for productivity and safety applications as well as scientific evaluation data of this framework on an active construction site.